The Implementation of The Mandatory Nature of Rasulullah in The Character Development of Students Through Learning of Akidah Akhlak - Uky Fatanun Fiqih; Muhammad Hanief; Sutarno Sutarno (Nazhruna: Jurnal Pendidikan Islam, 2022)
The purpose of this article is to analyze the learning planning of the aqidah akhlak, analyze the implementation of learning and analyze the evaluation of the learning that has been carried out. The research methodology used is a qualitative type with a case study approach. The data collection technique used in-depth interviews, participatory observation, and documentation, while the data checking technique used the credibility test, transferability test, dependability test, and confirmability test. The subjects in this study were students of Madrasah Aliyah Nurul Hasan Ngraho. From the research conducted from February to April 2022, this article generates 1) the planning carried out in learning akidah akhlak used instructions from the syllabus and lesson plans; 2) the implementation of learning in improving character is aimed at learning using Islamic boarding school techniques, muhadhoroh activities, reading the yellow book, sorogan, and munaqosah madrasa activities; 3) learning evaluation at MA Nurul Hasan includes PH, PTS, PAS/PAT, and madrasa exams.